2016
DOI: 10.1097/aog.0000000000001750
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cystoscopic Evaluation of Ureteral Patency

Abstract: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02476448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Prior studies have used either 100 or 200mg without significant evidence to support either doses. 7,8,9,10 Our results support the routine use of 200mg to improve outcomes. We also found that lower urine output intraoperatively is associated with increased efficacy of phenazopyridine.…”
Section: Commentsupporting
confidence: 64%
“…Prior studies have used either 100 or 200mg without significant evidence to support either doses. 7,8,9,10 Our results support the routine use of 200mg to improve outcomes. We also found that lower urine output intraoperatively is associated with increased efficacy of phenazopyridine.…”
Section: Commentsupporting
confidence: 64%
“…This dose is lower than those used in recent studies. 20 Three cases of hypotension requiring medical treatment were observed. This side effect was not mentioned in a study in which this low dose was used.…”
Section: Discussionmentioning
confidence: 99%
“…First, cystoscopy was not terminated in any of the cases before the surgeon and his assistants confirmed satisfactory bilateral ureter jet streams. Second, the use of saline is certainly acceptable by gynecologists and urologists and has served as the control arm in published clinical trials aiming to find alternatives to indigo carmine [19,20].…”
Section: Commentmentioning
confidence: 99%